Building a Resilient Society With the Special Economic Zone Concept: A Defense Economic Perspective - Al-Mujaddid, Toriq Furqon; Yulivan, Ivan; Prakoso, Lukman Yudho (The Republic of Indonesia Defense University, 2024)
This study explores the concept of Special Economic Zones as a strategy for building economic resilience in communities facing contemporary global challenges. Through a systematic literature review, this study analyzes Special Economic Zones’ implementation, contributions, and integration with Defense Economic theory. The study reveals that successful special economic zones are characterized by sector integration, innovation focus, multi-stakeholder involvement, increased productivity, and job creation. Cities adopting this model demonstrate 40% higher economic resilience to external shocks than conventional development approaches. The Special Economic Zone concept contributes to economic resilience through integrated innovation ecosystems, reduction of inequality, strengthening of supply chains, and promotion of green economy transitions. Its integration with Defense Economic theory introduces concepts like functional redundancy and dynamic resilience, enhancing adaptability to market changes and technological advancements. The study also highlights the importance of cybersecurity in maintaining economic resilience in the digital age. While the Special Economic Zone model shows promise in fostering sustainable development and economic resilience, challenges remain, particularly in developing countries, including infrastructure limitations and skills gaps. The research recommends a gradual implementation approach tailored to local contexts, emphasizing digital technology integration and human capital development.